Preventing Early Reading Failure: An Argument. (April 2015) - Morris, Darrell
Abstract: Across the pendulum‐like changes in beginning reading instruction over the past 30 years, three interrelated ideas emerge as the key to preventing reading failure in kindergarten and first grade: (1) an interesting, carefully‐leveled book curriculum; (2) a leveled phonics curriculum; and (3) a well‐trained teacher who knows how to integrate guided reading and phonics to meet the changing needs of struggling readers. A practicum (i.e., teachers tutoring one‐on‐one under the supervision of an expert coach) is deemed the best way to develop needed teacher expertise. Although investing in teacher knowledge and skill presents challenges (e.g., finding time, finding a coach, funding the training), it represents a school's best chance of breaking the cycle of early reading failure.